A Study on Infusing and Expanding Clean and Green Learning Spaces on Campus - Naik, Santosh Madeva; Bandi, Surendra; Mahajan, Hema; Waiker, Deepak; Gadhia, Deepak (Journal of Engineering Education Transformations, 2021)
Engineering education is not merely studying different subjects but also acquiring practical knowledge to implement in real-life circumstances. Mechanical engineering is a stream of engineering where students can focus on practical implementation of different concepts to make human life better. This study is inspired from clean & green campus program organized by IUCEE, where experiments on different types of renewable energy demonstrated and also emphasized on its usages in real life to make our environment clean and green. This study implemented different styles and experiments in mechanical engineering to enhance students’ learning on renewable energy related concepts. This study has conducted some of the activities in the campus to make campus green and clean so that students can understand the importance of it and can explore themselves to further execute their ideas. In this paper, an attempt is made to provide details about the student’s involvement in clean and green campus activity where students will be involved in energy audit, wastage management, water management team activity. This paper briefly summarizes the learning achieved through a faculty development program on clean and green energy campuses. This work comes with limitations and scope for future work in multiple aspects which are described in the complete paper.